PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PEGAWAI PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG (KPKNL) MEDAN - Pandapotan Na Uli Sun Siregar; Nazlah Rachma Panggabean; Dearma Sariani Sinaga; Rina Sevtina Sitorus (Lembaga Penelitian dan Pengabdian Masyarakat Universitass Darma Agung, 2020)
This study aims at finding whether there is an influence of motivation and work environment on the performance of Medan KPKNL employees. The hypothesis is that there is motivation and work environment motivation for the performance of KPKNL Medan employees. The sample used in this study is a saturated sample, which uses all members of the population as a sample obtained by 36 people, using the data collection methods Observation, Interview and Questionnaire. The method used by the author is Multiple Linear Regression Analysis Method, Classic Assumption Test, Coefficient Test, F Test and Determination Coefficient Test (R2). The results obtained from the regression equation obtained are Y = 15.866 + 0.424X1 + 0.069X2, which means that the significant performance of employees in Medan KPKNL. These results were obtained based on t count (2,210)> t table values ​​(1,690) and a significance value of 0.034 <0.05 was obtained. There is no influence of the work environment on employee performance in the Medan KNPL. These results are known because t value (0.342) < t table value (1.690) and found the significance value of 0.735 > 0.05. Simultaneously motivation and work environment on affect employee performance in KPKNL Medan. These results are known from the calculation of F value (6.795) greater than the F table value (3.28), while the significance value obtained is 0.003 < 0.05. The coefficient of determination obtained is 0.249 which means that 24.9% of the Performance of Medan KPKNL Employees (Y) is required by variations of the two independent variables, namely Motivation (X1) and Work Environment (X2) while the remaining 75.1% was influenced by other variables not examined.